The power Of why simple questions that lead to success - Lang, Amanda (Toronto Collins, 2012)
The urge to question is natural for small children?just ask any parent. But few of us are aware that it is also one of the most vital tools for success. In The Power of Why, Amanda Lang shows how curiosity and the ability to ask the right questions fuels innovation and can drive change not just in business but also in our personal lives.
Includes index
Keywords: Leadership